Bounded Rationality : Heuristics, Judgment, and Public Policy - Dhami, Sanjit; Sunstein, Cass R. (Cambridge, Massachusetts ; London, England : The MIT Press, 2022)
"An accessible and self-contained treatment of the current state of thinking about rationality in economics and other social sciences"--
Includes bibliographical references and index.
Keywords: Rational choice theory; Rational choice theory -- Mathematical models; Mathematical optimization; Social sciences -- Methodology